Determination of Diiodohydroxyquinoline Using UV-Visible and Atomic Absorption Spectrometry - NEJEM, R.M.; ISSA, M.M.; EL-ABADLA, N.S.; AL-KHOLY, M.; SALEH, A.A. (Asian Journal of Chemistry, 2010)
Three novel methods were developed for the determination of diiodohydroxyquinoline based on UV-Visible and atomic absorption spectrometry (AAS). Two UV-Visible sensitive methods based on the oxidation of diiodohydroxyquinoline by iron(III) and the produced iron(II) reacted with potassium ferricynide or 1,10-phenanthroline forming Prussian blue colour (Method I) or red colour complex [method(II)], respectively. The AAS method is based on the extraction of the excess iron(III) in the oxidation reaction of diiodohydroxyquinoline/iron(III). The iron(II) in the aqueous layer was aspirated into air-acetylene flame. The reactions have been evaluated to obtain optimum experimental conditions. Linear responses were exhibited over the ranges 2.0-20.0, 1.0-10.0 and 0.2-2.0 μg mL-1 for method I, method II and AAS, respectively. A high sensitivity is recorded as 0.091, 0.074 and 0.028 μg mL-1 for the proposed methods I and II and AAS, respectively. The limit of detection of diiodohydroxyquinoline by method I and II and AAS method were 0.2, 0.17 and 0.07 μg mL-1, respectively. The developed methods were applied for the assay of the drug substance in its commercial formulation. The results were statistically compared with official method using t- and f- tests at p < 0.05. The intra and inter-assay coefficients of variation were less than 6 % and the recoveries ranged from 94.0 to 102.5 %.